2020
DOI: 10.3390/ijms21124282
|View full text |Cite
|
Sign up to set email alerts
|

How Do Post-Translational Modifications Influence the Pathomechanistic Landscape of Huntington’s Disease? A Comprehensive Review

Abstract: Huntington’s disease (HD) is an autosomal dominant inherited neurodegenerative disorder characterized by the loss of motor control and cognitive ability, which eventually leads to death. The mutant huntingtin protein (HTT) exhibits an expansion of a polyglutamine repeat. The mechanism of pathogenesis is still not fully characterized; however, evidence suggests that post-translational modifications (PTMs) of HTT and upstream and downstream proteins of neuronal signaling pathways are involved. The determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 267 publications
(324 reference statements)
1
27
0
Order By: Relevance
“…TGF-β1 induces the p85 subunit of PI3K to be recruited into focal adhesion kinase (FAK) ( Vallée and Lecarpentier 2019 ). PI3K activates Akt by phosphorylation at the thr308 and ser473 sites ( Lontay et al, 2020 ). Moreover, TGF-β1 activates Akt signaling through p38 mitogen–activated protein kinase (MAPK) and FAK ( Choi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 induces the p85 subunit of PI3K to be recruited into focal adhesion kinase (FAK) ( Vallée and Lecarpentier 2019 ). PI3K activates Akt by phosphorylation at the thr308 and ser473 sites ( Lontay et al, 2020 ). Moreover, TGF-β1 activates Akt signaling through p38 mitogen–activated protein kinase (MAPK) and FAK ( Choi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of promoting palmitoylation of HTT and other substrates may be mediated by increased mHTT clearance, or reduced proteolytic cleavage of mHTT by caspase 6 (CASP6) at D586. We have indeed recently shown that CASP6 is palmitoylated by HIP14, resulting in CASP6 inactivation (Lontay et al, 2020;Skotte et al, 2017) Brain lysates from 6-month-old YAC128 and littermate controls (WT), BACHD and WT, humanized Hu97/18 and Hu18/18, Hu128/21 and Hu21/21 mice were subjected to the ABE assay. The palmitoylation signal (HAM+) is shown in the top panels for each mouse line and protein, and the total protein immunoprecipitated is presented in the corresponding bottom panel.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al, 2014;Yanai et al, 2006). These PTMs regulate subcellular localization, protein-protein interactions, aggregation and clearance which modulates the toxicity of mutant HTT (mHTT) (Atwal et al, 2007;Cariulo et al, 2017;Caron et al, 2013;Kratter et al, 2016;Lontay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This observation in combination with previous observations from our group on the cross-talk between T3 phosphorylation and K6 acetylation underscores the importance of conducting further studies to elucidate the role of cross-talk among PTMs in the regulation of Htt aggregation, especially since several PTMs are known to cluster in a short sequence motifs throughout the Htt protein (Figure 1a). 17,40 For example, most of the proteolytic sites identified on Htt are flanked by phosphorylation residues, indicating possible cross-talk between phosphorylation and proteolysis. 6 Although several studies have investigated the aggregation propensity of various N-terminal Htt fragments in different cellular and animal HD models, characterization of the aggregation properties of these fragments was limited to quantifying the number of inclusions and their size or shape.…”
Section: Discussionmentioning
confidence: 99%